PD-1 limits differentiation and plasticity of Tc17 cells - Arra, Aditya; Lingel, Holger; Pierau, Mandy; Brunner-Weinzierl, Monika C. (Frontiers in Immunology, 2023)
Blockade of surface co-inhibitory receptor programmed cell death-1 (PD-1; CD279) has been established as an important immunotherapeutic approach to treat malignancies. On a cellular level, PD-1 is demonstrated to be of particular importance in inhibiting differentiation and effector function of cytotoxic Tc1 cells (CTLs). Nevertheless, the role of PD-1 in modulating interleukin (IL)-17-producing CD8+ T-cells (Tc17 cells), which generally display suppressed cytotoxic nature, is not well understood. To evaluate the impact of PD-1 in Tc17 responses, we examined its functioning using different in vitro and in vivo models. Upon activation of CD8+ T-cells in Tc17 environment, we found that PD-1 was rapidly expressed on the surface of CD8+ T-cells and triggered a T-cell-internal mechanism that inhibited the expression of IL-17 and Tc17-supporting transcription factors pSTAT3 and RORγt. Expression of type17-polarising cytokine IL-21 and the receptor for IL-23 were also suppressed. Intriguingly, adoptively transferred, PD-1-/- Tc17 cells were highly efficient in rejection of established B16 melanoma in vivo and displayed Tc1 like characteristics ex vivo. When using IL-17A-eGFP reporter mice for in vitro fate tracking, IL-17A-eGFP expressing cells lacking PD-1 signaling upon re-stimulation with IL-12 quickly acquired Tc1 characteristics such as IFN-γ, and granzyme B expression, implicating lineage independent upregulation of CTL-characteristics that are needed for tumor control. In line with plasticity characteristics, absence of PD-1 signaling in Tc17 cells increased the expression of the stemness and persistence-associated molecules TCF1 and BCL6. Thus, PD-1 plays a central role in the specific suppression of Tc17 differentiation and its plasticity in relation to CTL-driven tumor rejection, which provides further explanation as to why the blockade of PD-1 is such an efficient therapeutic target for inducing tumor rejection.